2005
DOI: 10.1590/s1677-04202005000200004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on polyunsaturated fatty acid accumulation in soybean seeds

Abstract: Soybean oil contains around 60 % of polyunsaturated fatty acids, which are responsible for the low oxidative stability of soy-derived products. Soybean lines with low linolenic acid content can be obtained by genetic manipulation; however, a high proportion of the variation in fatty acids content is due to environmental factors. This work aimed to determine the effect of temperature on oil composition and on the activity of the enzymes CDP-choline:1,2-diacylglycerolcholine phosphotransferase (CPT) and acyl-CoA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 25 publications
0
26
0
1
Order By: Relevance
“…Hurburgh et al (1987) studied soybean samples from grain elevators in four states of the United States. Lannal et al (2005) reported that the content of linolenic acid increased when soybean was cultivated at lower temperatures. They also found that the decrease of protein content was greater than the increase of oil in the hot drier regions.…”
mentioning
confidence: 99%
“…Hurburgh et al (1987) studied soybean samples from grain elevators in four states of the United States. Lannal et al (2005) reported that the content of linolenic acid increased when soybean was cultivated at lower temperatures. They also found that the decrease of protein content was greater than the increase of oil in the hot drier regions.…”
mentioning
confidence: 99%
“…As these genes have been studied for the improvement of soybean oil quality (Lanna et al, 2005;Lima, 2005;Martins, 2007;Sousa, 2007), the presence of at least one seed-specific gene model was expected. However, this was not observed, and the gene models were shown to be expressed in different tissues.…”
Section: Glyma02g14210mentioning
confidence: 99%
“…LPCAT activity affects the incorporation of fatty acids into the sn-2 position of PC where polyunsaturated fatty acids are formed; therefore, it indirectly influences the composition of seed TAGs (Fukurawa-Stoffer et al, 2003). The exchange of acyl groups between CoA and acyl-phosphatidylcholine is important for regulating the quality of polyunsaturated fatty acids in the acyl-CoA pool for oil synthesis in developing seeds (Lanna et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In the 1980s, UFV included in the objectives of its breeding program the quality improvement of soybeans for human consumption, including better taste, levels of oil and protein, elimination of antinutritional factors, reduction of polysaccharides, altered levels of unsaturated fatty acids and others (Pereira et al 1992, Araújo et al 1997, Moreira et al 1997, Utumi et al 1998, Chiari et al 2004, Lanna et al 2005, Sediyama et al 2005, Moraes et al 2006, Barros et al 2008, Teixeira et al 2012. Simultaneously, the use of biotechnology tools became part of the routine in the work of soybean breeding (Alzate-Marin et al 1996, Moreira et al 1997, Schuster et al 2001, Moraes et al 2006.…”
Section: Soybeanmentioning
confidence: 99%